Pre- and peri-implantation Zika virus infection impairs fetal development by targeting trophectoderm cells - Lei Tan (Nature Portfolio, 2019)
Here, using human cells and mouse models, the authors show that Zika virus can infect preimplantation trophectoderm. Pre-implantation infection can affect nervous system development and survival of neural progenitors, and can result in miscarriage or spontaneous abortion.